Gender differences among new claimants of Incapacity Benefit - Kemp, P; Davidson, J (Cambridge University Press, 2009)
The academic literature on incapacity benefits in Britain is dominated by debates about 'hidden unemployment', particularly in relation to working-age men in the industrial and former coalmining areas. Although women account for two-fifths of all claimants, they have been given relatively little attention in the literature on incapacity benefits. This article draws on a representative survey of recent claimants of Incapacity Benefit (IB) in Britain to compare the situation of men and women aged under 60. It shows that there are significant differences in their characteristics and circumstances and in their routes onto this benefit. It is concluded that academic debates in Britain need to take into account the differences between women and men in order to reach a more complete understanding of the role of IB in the post-industrial economy.